2015
DOI: 10.1152/japplphysiol.00287.2015
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic lymphocytes induce progenitor cell mobilization after exercise

Abstract: There is evidence that apoptotic cells and their components have immunmodulatory properties and signaling function. The present study investigated first whether exercise-induced apoptosis and exercise-induced mobilization of progenitor cells are similarly affected by subjects' training status and, second, whether the appearance of dying cells in the circulation might mobilize progenitor cells. CD1 SWISS mice were subjected to a 10-wk endurance training using free wheel running or served as untrained controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…In addition, 24 h after exercise, a small number of apoptotic lymphocytes accumulate in bone marrow and blood coinciding with a mobilization of hematopoietic stem cells [17]. Further, injecting apoptotic lymphocytes (or their supernatant) into the bloodstream stimulates hematopoietic stem cell mobilization within 2 h [17]. These observations support the proposal that exercise reverses T cell immunosenescence by 'making immunological space' [18].…”
Section: Exercise and Changes To Immune Cell Frequency And Functionalsupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, 24 h after exercise, a small number of apoptotic lymphocytes accumulate in bone marrow and blood coinciding with a mobilization of hematopoietic stem cells [17]. Further, injecting apoptotic lymphocytes (or their supernatant) into the bloodstream stimulates hematopoietic stem cell mobilization within 2 h [17]. These observations support the proposal that exercise reverses T cell immunosenescence by 'making immunological space' [18].…”
Section: Exercise and Changes To Immune Cell Frequency And Functionalsupporting
confidence: 61%
“…Pivotal research by Kruger and colleagues, using fluorescent cell tracking in rodents, showed that T cells are redeployed to the gut, lungs, and bone marrow following exercise [16] reflecting heightened immune-surveillance at sites where pathogens are likely to be encountered (gut, lungs) and heightened immuno-regulatory activities (in bone marrow). In addition, 24 h after exercise, a small number of apoptotic lymphocytes accumulate in bone marrow and blood coinciding with a mobilization of hematopoietic stem cells [17]. Further, injecting apoptotic lymphocytes (or their supernatant) into the bloodstream stimulates hematopoietic stem cell mobilization within 2 h [17].…”
Section: Exercise and Changes To Immune Cell Frequency And Functionalmentioning
confidence: 99%
“…For example, a recent murine study has shown that 24 h after an acute bout of exercise, lymphocytes undergo apoptosis in peripheral blood and bone marrow, which occurs in parallel with an increase of haematopoietic stem cells at these sites (Mooren and Kruger 2015a ). Subsequent experiments showed that after inducing apoptosis in splenic lymphocytes from resting mice by H 2 O 2 exposure, and injecting apoptotic cells (and apoptotic supernatant separately), into the bloodstream of other resting mice, there was a substantial mobilisation of haematopoietic stem cells 2 h later (Mooren and Kruger 2015a ). These mobilised haematopoietic stem cells might travel to the thymus (or potentially extra-thymic sites) and develop into naïve T cells (Radtke et al 2013 ).…”
Section: Is the Size Of Immunological “Space” Fixed?mentioning
confidence: 99%
“…Similarly, exercise also redeploys T cells to the Peyer"s patches and bone marrow (19,20) and this is likely governed by other site-specific homing molecules like LPAM-1 (37) or VLA-4 (23, 26) rather than CLA. This allocation of certain cells to defined parts of the body might represent a homeostatic immune-surveillance response (10), or, instead, it has been hypothesised that senescent T cells are mobilised into the blood to facilitate their subsequent apoptosis in peripheral tissues (21,34), which may contribute to progenitor cell mobilisation after exercise (24). With regards to cutaneous surveillance against tumours and stressed tissue cells, it is unlikely this is tasked by αβ CD8+ T cells alone (13), and is likely supported by γδ T cells and NK cells, which are highly responsive to acute stress (1,6), and have the migratory capacity to enter cutaneous sites (13).…”
Section: Effects Of Hiie and Continuous Exercise On The Numbers Of Nkmentioning
confidence: 99%